Neutral But Better : The Possibility of Null Hierarchies - Garcia, Andrés G. (Acta Analytica, 2026)
Can two items both be neutral in value yet differ in rank? I argue that they can, with significant implications: not everything neutral should be treated equally. This challenges the widespread assumption that neutral value marks a point of evaluative equivalence. I defend the intuitive case for neutral hierarchies through examples from aesthetics and welfare, then show that both major accounts of neutral value—comparative and non-comparative—can accommodate such hierarchies once divorced from certain theoretical commitments.
Keywords: Betterness; Fitting attitudes; Indifference; Neutral value